Physical activity levels and weight control status by body mass index, among adults - National Health and Nutrition Examination Survey 1999-2004 - Kohl Harold W; Yore Michelle M; Kruger Judy (BMC, 2008)
Abstract Background Adequate levels of physical activity can assist with weight control efforts, however, only a modest number of national studies have examined the physical activity patterns by weight control status. This article aims to describe patterns of physical activity among men and women who reported engaging in weight control practices. Methods Data from the National Health and Nutrition Examination Survey (1999-2004) were used. The sample included 14,388 adults (aged ≥ 18 years), with measured weights and heights from which body mass index (BMI) (weight/height2; kg/m2) was calculated. Analyses were performed to describe the prevalence of engaging in levels of physical activity (< 150-630 minutes/week) by three levels of weight control status (trying to lose weight, trying to maintain weight, and not trying to lose/maintain weight). We also examined the association between physical activity level and weight control status by BMI. Results The prevalence of low levels of physical activity (< 150 minutes/week) was highest among those not trying to lose/maintain weight (77.7% men, 81.2% women), than those trying to lose, or maintain weight (64.2%-59.7% men, 68.1%-66.7% women). Significantly more men than women engaged in higher volumes of physical activity (p < 0.001). Among overweight men, those trying to lose weight were more likely to engage in 150-420 minutes/week (OR = 2.2, 95%CI 1.8-2.9) than those not trying to lose/maintain weight. Similarly, overweight women who were trying to lose weight were more likely to engage in 150-420 minutes/week (OR = 2.8, 95%CI 2.1-3.7) than were to those not trying to lose/maintain weight. Conclusion Despite people's intentions to lose or maintain their weight, the majority of adults do not engage even in the minimum recommended level of physical activity. However, the prevalence of engaging in high levels of physical activity (150-420 minutes/week) was highest among those trying to lose or maintain weight than were with those not trying to lose/maintain weight. Regardless of weight control status, all adults should be encouraged to engage in regular physical activity.